Case study of Legg-Calvé-Perthes disease observed in Radom (Poland, 18th–19th century) with literature review - Myszka, Anna; Mańkowska-Pliszka, Hanna; Rzeźnicka, Ewa; Dąbkowska, Agnieszka; Tomczyk, Jacek (Anthropological Review, 2023)
The aim of this study is to present the pathological lesions observed in a skeleton (male, about 35–38 years old) from Radom (Poland), dated to the 18th–19th century. Bone changes were observed in both femurs and both pelvic bones. The head of the femur is enlarged and deformed, described as “mushroom-shaped”, with areas of smooth cortex and cavities, or possible cystic residues. The neck of femur is short and thick. The bone shaft and distal epiphysis do not show any changes. The changes were also observed in both acetabularies of the hip joint (marginal bone formation, subchondral bone remodelling). Radiographic images show bilateral necrosis of the femoral head. There is a significant sclerotization of the femoral head, with a discrete visible crescent sign. These macroscopic and radiological changes match the symptoms associated with Legg-Calvé-Perthes disease. This is the first case of the disease described in bioarchaeological materials from Poland.